2023
DOI: 10.1055/a-2129-7254
|View full text |Cite
|
Sign up to set email alerts
|

Texture and color enhancement imaging versus high definition white-light endoscopy for detection of colorectal neoplasia: a randomized trial

Abstract: BACKGROUND Texture-and-Color-Enhancing-Imaging(TXI, Olympus, Japan) was recently proposed as a substitute to standard high-definition white-light(WLI) to increase lesion detection during colonoscopy. We performed an international, multicenter randomized trial to assess the efficacy of TXI in detection of colorectal neoplasia. METHODS We enrolled consecutive patients ≥40 years old undergoing screening, surveillance or diagnostic colonoscopies at 5 centers (Italy, Germany, Japan) from September 2021 through Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recently, a multicenter randomized controlled trial indicated that, compared to WLI, TXI improves the detection of colorectal neoplastic lesions. 26 This study found that TXI increased the detection of polyps <10 mm in size, both in the proximal and in the distal colon and both in non‐polypoid and polypoid lesions. However, the previous generation of colonoscopes (190 and 290 series) was also included.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, a multicenter randomized controlled trial indicated that, compared to WLI, TXI improves the detection of colorectal neoplastic lesions. 26 This study found that TXI increased the detection of polyps <10 mm in size, both in the proximal and in the distal colon and both in non‐polypoid and polypoid lesions. However, the previous generation of colonoscopes (190 and 290 series) was also included.…”
Section: Discussionmentioning
confidence: 57%
“…Color contrast enhancement technologies, such as LCI, have been developed to improve the visualization of these lesions, which are challenging to detect with WLI. In the only previous tandem study evaluating pSSLMR with LCI, no significant difference was found, but the Olympus), with some promising results [33].…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…In summary, even though LCI appears to be the most promising modality among the currently available enhanced image contrast systems, our data challenge its benefit and should prompt consideration regarding the future optimization of this technology. The development of a new generation of virtual chromoendoscopy is underway, such as texture and color enhancement imaging, with some promising results [32].…”
Section: Wlimentioning
confidence: 99%
“…The beauty of the current study by Antonelli et al [3] is the simplicity of the technique. The new-generation virtual chromoendoscopy is already integrated into the new video processor and the technique is available by simply pressing a button.…”
mentioning
confidence: 86%